P129 Systematic Review And Meta-analysis Of Cross-sectional Studies On Arc Welding Fume Effects And Obstructive Lung Disease. (10th November 2014) - Marongiu, A; Minelli, C; Canova, C; Schofield, S; Szram, J; Cullinan, P
Abstract : Introduction and objectives: Exposure to the complex metal-rich aerosol produced by arc welding is putatively linked to obstructive lung disease in welders through a mechanism of oxidative stress. Given that published studies have been mainly conducted by means of cross-sectional surveys, this research aims systematically to review these; we have previously published a similar review of (the many fewer) longitudinal studies on welders' lung function decline. Methods: Medline, Embase and Web of Science were searched up to July 2013 by combining two blocks for exposure (welding fume) and outcomes (FEV1, FVC, FEV1 /FVC%, asthma, acute and chronic bronchitis, dyspnoea and wheezing) both containing free text keywords and MeSH terms. Double data extraction was performed independently. To explore possible causes of heterogeneity a subgroup analysis was undertaken to account for country income level, participants' smoking status and welders' age. Results: Fifty-six cross-sectional studies were identified and 40 were included in the review. Of these, 35 were included in a meta-analysis; lung function was measured in 22 studies and symptoms in 30 studies. Compared with non-welders, welding was associated with a statistically significant reduction in FEV1 (SMD= -0.34; 95% CI, -0.57, -0.12; I 2 =92%) and FEV1 /FVC% (SMD= -0.51; 95% CI, -0.94, -0.08; I 2 =96%). The substantial heterogeneity in both outcomes was explored further but no subgroup analyses explained it. FVC reduction with welding exposure was not statistically significant and highly heterogeneous. Welding was associated with asthma (OR=1.65, 95% CI, 1.14, 2.37; I 2 =0%), acute bronchitis (OR=1.61, 95% CI, 1.15, 2.27; I 2 =11%), chronic bronchitis after excluding a large study 1 (1.92, 95% CI, 1.50, 2.46; I 2 =40%), dyspnoea in medium/low income countries (OR=3.54, 95% CI, 1.96, 5.08; I 2 =0%) and wheezing among non-smokers (OR=9.06, 95% CI, 3.75, 21.9; I 2 =0%). All risk estimates for symptoms were higher in medium/low income countries. Conclusions: Welding fume exposure has a negative effect on the respiratory health of workers, possibly leading to obstructive lung disease and increasing the risk of respiratory symptoms particularly in medium/low income countries. Reference: Groth M, Lyngenbo O. Respiratory symptoms in Danish welders. Scand J Soc Med, 1989;17(4):p. 271–6